2016
DOI: 10.1590/1678-98652016000300013
|View full text |Cite
|
Sign up to set email alerts
|

Reflection on sports nutrition: Where we come from, where we are, and where we are headed

Abstract: From a historical perspective of athletes' eating practices, the advancement of science and the provision of food in the modern Olympic Games, the author seeks to show that many challenges in practicing Sports Nutrition have their roots in how these processes were built. This essay aims to provide arguments for a reflection on the work of dietitians in the sports' scenario considering the growth of interest in this area, as well as the hosting of major sports events in Brazil. The professional training and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…It was also observed that athletes' discourse is rich in dietary beliefs related to the goals of weight loss and performance 31,32 . According to Juzwiak 33 , these beliefs can be explained by the existence of a gap between the scientific knowledge and the dissemination of information directed to the athlete through social networks and media or by colleagues and unskilled professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed that athletes' discourse is rich in dietary beliefs related to the goals of weight loss and performance 31,32 . According to Juzwiak 33 , these beliefs can be explained by the existence of a gap between the scientific knowledge and the dissemination of information directed to the athlete through social networks and media or by colleagues and unskilled professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, deepening the understanding of the set of representations and meanings involved in athletes' food choices and the socioeconomic and cultural aspects are fundamental for the development of effective interventions in their daily lives 23,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is not uncommon for athletes to be influenced by information in social media from colleagues and non-qualified professionals. Moreover, very rigid diets which do not take into consideration cultural aspects can lead athletes to quickly reject them 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional educational strategies to develop the athletes' autonomy in choosing healthy food are important steps to improve athletes' diets and thus optimizing their performance [36][37][38] . Educational strategies involving an understanding of athletes´ food beliefs and practices which encourage them to focus on their own diets have been suggested as being most effective 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Assim, pode-se compreender que "tomar suplementos alimentares" e seus consumos ou consumismos também se constituem como uma construção sociocultural em diferentes grupos e faixas etárias (KUWAE et al, 2015;JUZWIAK, 2016). Nesse sentido, o presente trabalho se orienta a partir das seguintes questões: como os praticantes de atividade física lidam com os suplementos alimentares nas academias ao longo do tempo?…”
Section: Considerações Iniciaisunclassified